الأصوات العربية بين الفصحى واللهجات؛ لهجة منطقة ورقلة عينة: Arabic phonemes between formal language and dialects. The dialect of the Ouargla region is a sample - دقناتي فضيلة (Maalim, 2022)
Each language has its own sound system, which distinguishes it from other languages; even if they are similar in the number of linguistic sounds; And the sounds in the same language differ in dialects that all belong to the same language. In our research paper, we will study the sounds of the classical Arabic language, and the change in performance in its dialects today, by presenting samples of the dialect of the Ouargla region.